2015
DOI: 10.1016/j.ajog.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of polymorphonuclear leukocytes has no effect on preterm delivery in a mouse model of Escherichia coli-induced labor

Abstract: Objective To investigate the role of polymorphonuclear leukocytes (PMNs) in a mouse model of E. coli-induced labor. Study Design Intraperitoneal injection of rabbit anti-mouse PMN antiserum or control was performed in CD-1 mice 29 hours and 5 hours prior to laparotomy and intrauterine injection of either killed E. coli or phosphate buffered saline on Day 14.5 of pregnancy. Preterm delivery was defined as delivery of at least one pup within 48 hours. Circulating leukocyte counts were determined manually or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(52 reference statements)
0
20
2
Order By: Relevance
“…According to a multi-center biomarker study of IUI, when compared to human data, the IL-6 levels in the AF in our study would be categorized as "severe inflammation" (28). Contrary to our data, studies in mice did not show a benefit to neutrophil depletion in protecting against LPS induced PTL (29,30). However, these mice had increased systemic concentrations of myeloid hematopoietic progenitors and myelopoietic cytokines G-CSF, IL-23, and IL-17 (31), presumably due to a "neurostat" mechanism sensing neutrophil depletion.…”
Section: Discussioncontrasting
confidence: 83%
“…According to a multi-center biomarker study of IUI, when compared to human data, the IL-6 levels in the AF in our study would be categorized as "severe inflammation" (28). Contrary to our data, studies in mice did not show a benefit to neutrophil depletion in protecting against LPS induced PTL (29,30). However, these mice had increased systemic concentrations of myeloid hematopoietic progenitors and myelopoietic cytokines G-CSF, IL-23, and IL-17 (31), presumably due to a "neurostat" mechanism sensing neutrophil depletion.…”
Section: Discussioncontrasting
confidence: 83%
“…Neutrophilderived pro-inflammatory mediators can trigger preterm labor and matrix metalloproteinases (MMPs) can weaken the collagen scaffolding, resulting in preterm rupture of membranes (156)(157)(158). However, studies in mice with systemic neutrophil depletion did not protect against inflammation-induced preterm birth (159,160). Although the reasons for the apparent contradiction are not clear, neutrophil depletion in mice causes a systemic up-regulation of G-CSF, IL-17, and IL-23, leading to hyper-cellular bone marrow as a homeostatic "neutrostat" mechanism to restore the blood neutrophil pool (161,162).…”
Section: Neutrophilsmentioning
confidence: 99%
“…However, two independent studies have demonstrated that depletion of neutrophils in mice treated with LPS did not prevent PTB, suggesting that infection-induced PTB does not require neutrophil infiltration. 78,79 Ongoing studies to understand the role of immune cells and inflammation in term and preterm cervical remodeling may provide insight into the distinct mechanisms that drive the prostaglandin-dependent and prostaglandin-independent pathways of cervical remodeling.…”
Section: Cervical Remodeling In Term and Preterm Birthmentioning
confidence: 99%